Robust Climate Change Adaptation for Environmental Flows in the Goulburn River, Australia - John, Andrew; Horne, Avril; Nathan, Rory; Fowler, Keirnan; Webb, J. Angus; Stewardson, Michael (Frontiers in Environmental Science, 2021)
Climate change presents severe risks for the implementation and success of environmental flows worldwide. Current environmental flow assessments tend to assume climate stationarity, so there is an urgent need for robust environmental flow programs that allow adaptation to changing flow regimes due to climate change. Designing and implementing robust environmental flow programs means ensuring environmental objectives are achieved under a range of uncertain, but plausible climate futures. We apply stress testing concepts previously adopted in water supply management to environmental flows at a catchment scale. We do this by exploring vulnerabilities in different river management metrics for current environmental flow arrangements in the Goulburn River, Australia, under non-stationary climatic conditions. Given the limitations of current environmental flows in supporting ecological outcomes under climate change, we tested three different adaptation options individually and in combination. Stress testing adaptation results showed that increasing environmental entitlements yielded the largest benefits in drier climate futures, whereas relaxing river capacity constraints (allowing more targeted delivery of environmental water) offered more benefits for current and wetter climates. Combining both these options led to greater than additive improvements in allocation reliability and reductions in environmental water shortfalls, and these improvements were achieved across a wider range of climatic conditions than possible with either of the individual options. However, adaptation may present additional risks to some ecological outcomes for wetter climates. Ultimately, there was a degree of plausible climate change beyond which none of the adaptation options considered were effective at improving ecological outcomes. This study demonstrates an important step for environmental flow assessments: evaluating the feasibility of environmental outcomes under climate change, and the intervention options that prove most robust under an uncertain future.